( x 2 0 1 9 + 1 ) 2 0
What is the sum of the coefficients of the terms with odd powers of x , when the expression above is completely expanded?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It will be the sum of odd combinations of 20, i.e.
n = 0 ∑ 9 C 2 n + 1 2 0
= 2 1 ⋅ 2 2 0
= 5 2 4 2 8 8
Doesnt It seems overrated?
Problem Loading...
Note Loading...
Set Loading...
Let u = x 2 0 1 9 . Then when the power of x is odd, the power of u is also odd. And we have:
( 1 + u ) 2 0 ( 1 − u ) 2 0 ( 1 + u ) 2 0 − ( 1 + u ) 2 0 2 ( 1 + u ) 2 0 − ( 1 + u ) 2 0 2 ( 2 ) 2 0 − ( 0 ) 2 0 = ( 0 2 0 ) + ( 1 2 0 ) u + ( 2 2 0 ) u 2 + ( 3 2 0 ) u 3 + ⋯ + ( 2 0 2 0 ) u 2 0 = ( 0 2 0 ) − ( 1 2 0 ) u + ( 2 2 0 ) u 2 − ( 3 2 0 ) u 3 + ⋯ + ( 2 0 2 0 ) u 2 0 = 2 ( ( 1 2 0 ) u + ( 3 2 0 ) u 3 + ( 5 1 0 ) u 5 + ⋯ + ( 1 9 2 0 ) u 1 9 ) = ( 1 2 0 ) u + ( 3 2 0 ) u 3 + ( 5 1 0 ) u 5 + ⋯ + ( 1 9 2 0 ) u 1 9 = ( 1 2 0 ) + ( 3 2 0 ) + ( 5 1 0 ) + ⋯ + ( 1 9 2 0 ) Putting u = 1
Note that the LHS is the sum of coefficients of odd powers of x , which is = 2 1 9 = 5 2 4 2 8 8 .